Predictably unpredictable: sport psychologists` experience of precarity working in elite sport organisations - Quartiroli, A.; Wagstaff, C. R. D.; Wren, B. (International Journal of Sport and Exercise Psychology, 2025)
There is growing body of literature that indicates that elite sport organisations are a volatile professional domain characterised by high levels of intentional change and widespread precarity for employees. Working within an interpretivist paradigm, and using a semi-structured interview guide, we conducted interviews with 12 (6 Male, 6 Female) Sport Psychology Professionals (SPPs) who had experience of working in elite sport organisations in the UK. Specifically, we aimed to construct a robust account of the professional precarity experienced by SPPs who had and had not been retained after 6 months of employment in their role. The interviewees had an average of 8 years of professional experience and were aged between 28 and 45 years. We developed four higher order themes which encompassed 11 lower order themes. The higher order themes were: (a) it`s like a sinking ship, there is no loyalty in elite sport; (b) you can`t be authentic when you are constantly under threat; (c) in a world that feels messy, you often feel alone and uncertain, and; (d) it costs to practice in elite sport. The results have the potential to significantly advance scholarly understanding of the challenges faced by SPPs practicing in elite sport organisations, while highlighting salient educational and training needs. These results have important implications for professional societies, regulatory bodies, and education and training institutions responsible for supporting and safeguarding SPPs` and their work in such environments. We also consider how SPPs may act as a recipient and a key social agent for these changes.